Analisis Penyebab Keterlambatan Proyek Konstruksi Transmisi dan Gardu Induk: Studi Kasus Unit Induk Pembangunan Jawa Bagian Timur dan Bali (UIP JBTB) - Prawidhana, Denta; Dinariyana, AAB (Universitas Trunojoyo Madura, 2024)
As many as 87.63% of PT PLN (Persero) UIP JBTB Transmission and Substation construction projects in the 2010-2023 range experienced delays. The purpose of this study is to determine the main factors that contribute to project delays from the perceptions of internal, supervision consultants, and contractors and provide suggestions to Management to minimize potential losses due to delays in project completion in the future. The methods used in this research are literature study, data collection through survey, data analysis, and conclusion. Data analysis is done quantitatively using Frequency Index and Relative Importance Index, Independent T Test, Cartesian Diagram, and 5 Why's. The results of this study indicate that there are 5 most influential variables in delays, namely delays in land acquisition, community social conflicts, labor shortages, delays in submitting drawings, and cash flow difficulties. Strategic steps to overcome delays in project completion are to select prospective land for transmission and substation construction projects on undisputed land, create a project security MoU by involving security forces either TNI or Polri, create a smoother financial flow system, create an easy and effective payment system in the project, and monitor the administrative process and create an easier and safer document management system.